2009
DOI: 10.1111/j.1365-2826.2009.01873.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Exposure to Low Levels of Oestradiol‐17β Affects Oestrous Cyclicity, Hypothalamic Norepinephrine and Serum Luteinising Hormone in Young Intact Rats

Abstract: Chronic exposure to oestrogens is known to inhibit the secretion of luteinising hormone (LH) in rats causing anovulation. Hypothalamic catecholamines, norepinephrine (NE) and dopamine (DA) play an important role in LH regulation. However, the effects of chronic exposure to low levels of oestradiol on hypothalamic catecholamines have not been investigated thoroughly. To study this, adult female Sprague-Dawley rats were either sham implanted or implanted with oestradiol-17ß (E2) pellets (20 ng/day) for 30 (E-30)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 40 publications
6
29
0
Order By: Relevance
“…However, E 2 exposure for 60 or 90 days resulted in a significant increase in serum E 2 levels (67.2 Ϯ 8.4 and 90.2 Ϯ 9.2 in E-60 and E-90 groups, respectively) (P Ͻ 0.05). This is most likely due to the presence of cystic follicles in the ovaries of these animals, as previously reported (24). Similarly, serum E 2 levels in OCE rats (94.2 Ϯ 22) were significantly higher compared with control and E-30 rats (P Ͻ 0.05).…”
Section: Effects Of Chronic E 2 Exposure On Estrous Cyclicity and Sersupporting
confidence: 68%
See 2 more Smart Citations
“…However, E 2 exposure for 60 or 90 days resulted in a significant increase in serum E 2 levels (67.2 Ϯ 8.4 and 90.2 Ϯ 9.2 in E-60 and E-90 groups, respectively) (P Ͻ 0.05). This is most likely due to the presence of cystic follicles in the ovaries of these animals, as previously reported (24). Similarly, serum E 2 levels in OCE rats (94.2 Ϯ 22) were significantly higher compared with control and E-30 rats (P Ͻ 0.05).…”
Section: Effects Of Chronic E 2 Exposure On Estrous Cyclicity and Sersupporting
confidence: 68%
“…Rats were provided food and water ad libitum. Estrous cyclicity was determined in young (3-4 mo old) and old (16 -18 mo old) rats by vaginal cytology (24). Young animals showing 4-to 5-day regular estrous cycles and old animals that exhibited estrous smears for more than 10 consecutive days (old constant estrous, OCE) were used in the experiments.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, repeated exposures to periodic increases in E2 during the course of normal reproductive cycles probably contribute to a reduction in hypothalamic catecholamines that causes a decrease in LH secretion and failure of ovulation leading to reproductive senescence 10 . We have found that a similar state of reproductive senescence can be induced in young animals that are exposed to low levels of E2 on a daily basis for 60 or 90 days 11 . Ovaries from old constant estrous (OCE) rats that are exposed to endogenous E2 during the course of their estrous cycles appear to be cystic and very similar to ovaries from young, E2-exposed rats.…”
Section: Introductionmentioning
confidence: 76%
“…Initially, the middle-aged female rats were either sham operated or bilaterally OVX and after a week of recovery, 30-day placebo or estrogen pellets [17β-estradiol (0.6 μg or 300 μg), Innovative Research America, Florida, USA] were implanted subcutaneously in the nape of the neck. The doses were selected based on a preliminary study in our laboratory and a published study [28,29]. At the end of the treatment period, the animals were sacrificed by decapitation between 08:00 to 10:00 h. Trunk blood was collected in Falcon tubes, serum was isolated and used for hormone assay.…”
Section: Treatmentmentioning
confidence: 99%